Laparoscopic gastrectomy for elderly patients with gastric cancer: A systematic review with meta-analysis. Issue 8 (February 2018) - Pan, Yu; Chen, Ke; Yu, Wei-hua; Maher, Hendi; Wang, Sui-han; Zhao, Hang-fen; Zheng, Xue-yong
Abstract: Background: Laparoscopic gastrectomy (LG) has been widely applied in patients with gastric cancer (GC). However, the safety and application value of LG in elderly patients with GC was still unclear. In this study, we aimed to evaluate the feasibility and safety of LG for elderly patients with GC using the meta-analysis. Methods: Studies comparing elderly patients and nonelderly patients who underwent LG for GC were reviewed and collected from the PubMed, EBSCO, Cochrane Library, and EMBASE. Outcomes such as operative results, postoperative recovery, and morbidity were compared and analyzed. The Review Manager 5.3 was used to portray the weighted mean difference (WMD) and odds ratio (OR) with a 95% confidence interval (CI). Results: Eleven observational studies with a total of 3275 patients were included. Compared with nonelderly patients, elderly patients had shorter operation time (WMD −10.46; 95% CI −17.06 to −3.86; P = .002), less retrieved lymph nodes (WMD −2.34; 95% CI −3.77 to −0.92; P = .001), delayed time to first flatus (WMD 0.31; 95% CI 0.10–0.51; P = .003), longer postoperative hospital stays (WMD 1.06; 95% CI 0.07–2.05; P = .04), higher risk for overall postoperative complication (OR 1.34; 95% CI 1.08–1.67; P = .009), nonsurgical postoperative complication (OR 1.98; 95% CI 1.24–3.15; P = .004), and postoperative pulmonary complication (OR: 3.09; 95% CI 1.68–5.68; P < .001). There was no significance between nonelderly patients and elderly patients regarding the estimated blood loss, incidences of surgical postoperative complication, surgical site infection, and ileus ( P > .05). Conclusion: Outcomes of LG for elderly patients were comparable to those in nonelderly patients. Age alone should not preclude LG in elderly patients.